Biological Distance Analysis and the Fate of the Gallina in the American Southwest. Issue 4 (2nd October 2017) - O'Donnell, Alexis; Ragsdale, Corey S.
Abstract : The Gallina heartland was abandoned around AD 1275. The fate of the Gallina people after this abandonment is not well understood. This study uses biological distance analysis to evaluate possible migratory patterns of the Gallina people after their decline. Is there evidence for population continuity of the Gallina in the Rio Grande Valley, or did cultural pressures drive them to more distant areas such as the Mogollon Rim or Greater Southwest? We use dental morphological data to compare individuals from Gallina with samples representing the Rio Grande Valley, as well as the Arizona Mountain Mogollon and Northern Mexico dating after AD 1300. Our results indicate the Gallina possibly migrated to the Middle Rio Grande region, and refute hypotheses that the Gallina people were culturally and biologically isolated from other American Southwest populations. We emphasize the importance of combining archaeological, linguistic, and biological data to evaluate migratory patterns of past populations.